Surface characterization of Au-ZnO nanowire films - Jamali-Sheini, Farid; Yousefi, Ramin; Patil, K. R. (Ceramics International, 2012)
Au-ZnO nanowire films have been synthesized by annealing Zn foils coated with a thin layer of gold. An X-ray diffraction study found that the synthesized ZnO consists mainly of a hexagonal wurtzite structure along with a small amount of AuZn3 phase. Scanning electron images showed that the ZnO wires extend to several microns in length. X-ray photoelectron spectroscopy studies confirmed the oxidation states of Au and Zn. An asymmetric O ls peak indicates the presence of oxygen in an oxide layer and O H groups on the films surfaces. Photoluminescence (PL) spectra showed different visible peaks for pre-annealed films, while for annealed films an UV peak appeared. In addition, the PL analysis showed that the overall intensity of photoluminescence decreased significantly after the films were annealed. Raman spectroscopy results also indicated that the crystalline quality of the films improved with annealing. This could be attributed to a decrease in oxygen vacancies and/or absorption of O-H groups on the surface of ZnO film. The highly hydrophilic surface with a water contact angle of similar to 155 degrees was obtained after annealing in air. (c) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Au-ZnO; Highly hydrophilic; Nanowires; XPS